Representation of Women’s Abortion Experiences in Jeritan Dalam Botol Short Stories By Intan Paramaditha: A Critical Discourse Analysis of Sara Mills' Perspective - Rakhmasari, Dwi Lia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Literary works have a big role in shaping and changing people's thoughts, feelings, attitudes, opinions, and behaviors about women. This is inseparable from the ideology of feminism of literary works, one of which is in the form of short stories (short stories) based on a gender perspective. This paper aims to describe Sara Mills feminist ideology using a procedure for simultaneous analysis of critical discourse. Based on this goal, the author encourages the author to study in a literature study entitled